HIF-1 sensor in detecting hypoxia tolerance at high altitude - Shaharuddin, Shazreen; Nik Abd Rahman, Nik Mohd Afizan; Masarudin, Mas Jaffri; Alamassi, Mohammedarfat N.; Ahmad Saad, Fathinul Fikri (Aerospace Medical Association, 2023)
INTRODUCTION: An episode of prolonged exposure to high altitude can cause hypoxia and have significant health consequences. In people with a high-altitude disorder, the body reacts by producing a protein called hypoxia-inducible factor (HIF), which triggers a series of physiological changes and serves a central role in the hypoxia response. Its activity is regulated by the oxygen-dependent degradation of the HIF-1α protein (HIF-1A gene). Therefore, the effects of low oxygen tension in high altitude were explored using fluorescent sensors of hypoxia. METHODS: The development of the sensor provided more sensitivity for detecting hypoxia by generating a calibration of optimized parameters such as reagent concentrations, reagent volumes, and device dimensions. RESULTS: There is a high sensitivity and specificity in detecting the changes of HIF-1α protein hypoxia using the feasibility hypoxia test. This would enable point-of-care (POC) testing and individual self-administration, resulting in faster and more accurate results that can be used for a robust diagnostic approach and enhanced health surveillance, particularly in high-altitude exposure.